2010
DOI: 10.1016/j.febslet.2010.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress response is involved in Mycobacterium tuberculosis protein ESAT‐6‐mediated apoptosis

Abstract: a b s t r a c tMycobacterium tuberculosis (Mtb) infection leads to the induction of the apoptotic response, which is associated with bacilli killing. The early secreted mycobacterial antigen ESAT-6 of Mtb has been shown to induce apoptosis in human macrophages and epithelial cells. In the present study, we demonstrate that the stimulation of human epithelial A549 cells by ESAT-6 induces the endoplasmic reticulum (ER) stress response. We observed that ESAT-6 treatment increases intracellular Ca 2+ concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 28 publications
10
104
0
Order By: Relevance
“…The connection between bacteria pathogen and UPR has been revealed for a long time [27,28], and recently, several studies proved the induction of apoptotic ER stress in intoxicated mammalian cells with Stxs [13]. In this study, we found that just like Stxs, rTcdB also induced the up-regulation of CHOP, ATF4, and PERK mRNA (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…The connection between bacteria pathogen and UPR has been revealed for a long time [27,28], and recently, several studies proved the induction of apoptotic ER stress in intoxicated mammalian cells with Stxs [13]. In this study, we found that just like Stxs, rTcdB also induced the up-regulation of CHOP, ATF4, and PERK mRNA (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…A second signal emanating from dead or dying macrophages appears to draw these macrophages to them, and their encased bacteria are then phagocytosed to create new infected cells. Indeed, RD1-competent mycobacteria also induce more apoptotic death of infected macrophages in the granuloma (Volkman et al 2004;Davis and Ramakrishnan 2009), consistent with studies showing that the RD1-encoded virulence determinant ESAT-6 can induce multiple programs associated with cell death in vitro Derrick and Morris 2007;van der Wel et al 2007;Choi et al 2010;Mishra et al 2010;Aguilo et al 2013). It would be predicted that the coordinated acceleration of new macrophage recruitment and infected macrophage apoptosis would be required to maximize bacterial expansion in the granuloma.…”
Section: Mechanistic Basis Of Bacterial Esx-1 Induced Granuloma Formasupporting
confidence: 58%
“…The EsxA protein of the ESX-1 system can form homo-and heterodimers that can insert into the host cell membrane to induce necrosis (Hsu et al 2003;de Jonge et al 2007;Smith et al 2008;Welin et al 2011). In contrast, other reports show that ectopic expression of EsxA and/or the incubation of cells with purified EsxA induce host cell apoptosis (Derrick and Morris 2007;Choi et al 2010). There is a clear consensus though in the literature that Mtb or Mm mutants deficient in esxA induce less cell death and that these mutants are also severely attenuated in the mouse and zebrafish model of tuberculosis (Abdallah et al 2007;DiGiuseppe Champion and Cox 2007;Ramakrishnan 2012).…”
Section: Mtb Genes Involved In Host Cell Programmed Necrosis Inductionmentioning
confidence: 85%